THE REINTERPRETATION OF JIHAD IN MODERN ISLAMIC DISCOURSE BETWEEN EXTREMISM AND PEACE - Dr. Ayesha Jadoon (Journal of Religion and Society, 2024)
The concept of jihad, one of the most debated and misunderstood tenets of Islam, has undergone significant reinterpretation in modern Islamic discourse, particularly in the context of extremism and peace. This study explores the evolving meanings of jihad within contemporary Islamic thought, examining how it has been appropriated by extremist groups to justify violence, while also being redefined by moderate scholars and peace advocates as a spiritual and ethical struggle for self-improvement and social justice. By analyzing key theological texts, scholarly interpretations, and the rhetoric of both extremist and moderate voices, this research highlights the divergent ways in which jihad is conceptualized in modern times. The study also investigates the historical and cultural factors that have contributed to these contrasting interpretations, including colonialism, globalization, and the politicization of religion. Through a critical examination of primary and secondary sources, including Qur’anic exegeses, fatwas, and contemporary Islamic literature, this research aims to provide a nuanced understanding of jihad that transcends simplistic binaries of violence and peace. The findings reveal that while extremist groups have weaponized jihad to legitimize acts of terror, many Islamic scholars and reformers have emphasized its original Qur’anic meaning as a struggle for moral and spiritual growth, as well as a commitment to justice and human dignity. This study concludes that the reinterpretation of jihad in modern Islamic discourse is not only a theological issue but also a socio-political one, with profound implications for global peace, interfaith dialogue, and the fight against religious extremism. By shedding light on the multifaceted nature of jihad, this research contributes to a more balanced and informed understanding of its role in contemporary Islam, offering insights into how it can be reclaimed as a force for peace and reconciliation in an increasingly polarized world. Keywords: Jihad, Islamic Discourse, Extremism, Peace, Qur’anic Interpretation, Modern Islam, Spiritual Struggle, Social Justice